RIGHT ISSUE (SUATU INSTRUMENT DERIVATIF SAHAM) - Atik Atiatun Nafisah Atik Atiatun Nafisah (LPPM STIA Banten, 2018)
The rights issue instrument is a stock derivative instrument that provides the right to buy new shares that will be issued by the issuer at a certain price and at a certain time has been determined. The rights issue process begins with a request for approval from the holders shares to issue new shares to obtain fresh funds. Then After obtaining approval, it is offered to the old shareholders who own it the right to purchase new shares (limited offering). This purchase right is usually already formulated by the company. If the old shareholders do not want to exercise the rights his rights, he can sell his rights to the public. However, there are several risks that will be accepted by investors after the rights issue, among others other things, dilution of share ownership, price dilution per share, decrease in dividend per share, obtaining dividends, and obtaining capital gains.